“Off-The-Shelf” allogeneic chimeric antigen receptor T-cell therapy for B-cell malignancies: current clinical evidence and challenges - Mohty, Razan; Lazaryan, Aleksandr (Frontiers in Oncology, 2024)
Chimeric antigen receptor T-cell therapy (CAR T) has revolutionized the treatment landscape for hematologic malignancies, notably B-cell non-Hodgkin lymphoma (B-NHL) and B-cell acute lymphoblastic leukemia (B-ALL). While autologous CAR T products have shown remarkable efficacy, their complex logistics, lengthy manufacturing process, and high costs impede widespread accessibility and pose therapeutic challenge especially for patients in rapid need for therapy. "Off-the-shelf" allogeneic CAR T-cell therapy (alloCAR T) has emerged as a promising alternative therapy, albeit experimental to date. AlloCARTs are derived from healthy donors, manufactured by batches and stored, making them available off-the-shelf which lowers financial burden. Various gene editing techniques have been employed to mitigate graft-versus-host disease (GVHD) and host-versus-graft (HvG) to enhance alloCAR T persistence. In this review, we summarize available manufacturing techniques, current evidence, and discuss challenges faced with the use of alloCAR Ts.